La sirvienta y el luchador: An Interpretation - Rojas G., Margarita (2018)
This study discusses the fourth novel in the series on the Aragón family, begun by Horacio Castellanos Moya in 2003 and completed in 2013. All the novels refer to the political history of El Salvador since 1944, and nearly all mention one event: the kidnapping and murder of the son of Alberto Aragón, which is finally narrated in La sirvienta y el luchador. This is carried out with an apparent simplicity that hides a skillful manipulation of narrative resources. The textual complexity requires an interpretation which goes beyond historical references and addresses the literary value of the text.